Have Teachers' Perceptions of Parental Engagement Changed Following COVID-19? Evidence from a Mixed-Methods Longitudinal Case Study - Cat Jones; Olympia Palikara (MDPI AG, 2023)
Parental engagement is of interest to teachers, school leaders, researchers, and policy makers as a key driver of pupil outcomes. Existing evidence suggests that parental engagement with learning in the home is most effective, but English schools often prioritise school-based events. However, the move to home-learning due to COVID-19 required parents and teachers to play different roles in relation to learning and in relation to each other. Little is known about how this has affected teachers' perceptions of parental engagement. This mixed-methods, longitudinal case study examined whether teachers' perceptions of parental engagement changed during COVID-19. Data was gathered from teachers at one large English primary school using interviews (n = 9) and questionnaires (n = 16). Data from before and after the school closures was compared. Teachers reported that parental engagement had become increasingly digital, flexible, and wellbeing-focussed during the school closures. However, teachers were pessimistic about the likelihood of retaining any benefits and their future plans remained focussed on school-based parental engagement events. Whilst school closures resulted in a temporary positive shift towards partnerships and family-centric parental engagement, teachers now need time and training to embed these changes. Without this, some of the potential benefits of the home-learning period may be lost.